2009
DOI: 10.2478/v10019-009-0024-x
|View full text |Cite
|
Sign up to set email alerts
|

Negative predictive value of F-18-FDG coincidence PET in patients with Hodgkin's disease and a residual mass after therapy: a retrospective diagnostic test study

Abstract: Background. The aim of the study was to asses the negative predictive value (NPV) of FDG-PET performed with triple-head coincidence gamma camera after the first-line therapy or salvage therapy in patients with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Recent studies have indicated that PET is useful in the follow-up of synovial sarcoma 1,23. PET/CT has also been used as a diagnostic tool for synovial sarcoma, as well as lymphoma 20,28,29. Charest et al .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated that PET is useful in the follow-up of synovial sarcoma 1,23. PET/CT has also been used as a diagnostic tool for synovial sarcoma, as well as lymphoma 20,28,29. Charest et al .…”
Section: Discussionmentioning
confidence: 99%
“…Although there has been some evidence that in the treatment of lymphoma patients the better response is associated with the prolonged disease-free survival, the correlation between the quality of response and the survival still remains unknown 49. Recently published studies have indicated that a better response to first-line treatment translates into an improved survival for patients with follicular lymphoma and also with other malignomas 10,11.…”
Section: Introductionmentioning
confidence: 99%
“… 3 , 4 Although there has been some evidence that in the treatment of lymphoma patients the better response is associated with the prolonged disease-free survival, the correlation between the quality of response and the survival still remains unknown. 4 9 Recently published studies have indicated that a better response to first-line treatment translates into an improved survival for patients with follicular lymphoma and also with other malignomas. 10 , 11 With our retrospective study we, therefore, wanted to assess the potential correlation between either the quality of response or the line of the rituximab treatment with both the overall survival (OS) and the disease-free survival (DFS) of patients with B-cell lymphomas.…”
Section: Introductionmentioning
confidence: 99%